Biomimetic superhydrophobic surfaces - Oliveira, Mariana B. (2014)
Inspiration from nature has been widely used in the development of new materials and in the improvement of their properties. Superhydrophobic surfaces inspired in species present in nature with highly water repellent self-cleaning properties — such as the well-known lotus leaf — are interesting examples of the biomimetic approach for the development of new materials and devices. The discovery of new applications from these materials in the biotechnology and biomedical fields was in wide expansion during the last years. As recent examples of application of surfaces highly repellent to water are implantable biomaterials with antiadherent properties for vascular grafts or with bactericidal properties. By patterning these surfaces with wettable regions, microfluidic devices and sensors for the simple and economical diagnosis/monitoring of diseases and cell studies were developed. Another relevant approach regarding patterned superhydrophobic surfaces is their use as chips for high-throughput combinatorial studies in tissue engineering and regenerative medicine. The use of these platforms allowed circumventing several limitations associated with state-of-the-art techniques. Considering the recent innovative approaches and the wide possibilities for future work using these surfaces, we consider that the development of biomimetic superhydrophobic surfaces and their application as innovative and affordable devices is a promising research area.